A loss of telocytes accompanies fibrosis of multiple organs in systemic sclerosis. Issue 2 (February 2014) - Manetti, Mirko; Rosa, Irene; Messerini, Luca; Guiducci, Serena; Matucci‐Cerinic, Marco; Ibba‐Manneschi, Lidia
Abstract Systemic sclerosis (SSc) is a complex connective tissue disease characterized by fibrosis of the skin and various internal organs. In SSc, telocytes, a peculiar type of stromal (interstitial) cells, display severe ultrastructural damages and are progressively lost from the clinically affected skin. The aim of the present work was to investigate the presence and distribution of telocytes in the internal organs of SSc patients. Archival paraffin‐embedded samples of gastric wall, myocardium and lung from SSc patients and controls were collected. Tissue sections were stained with Masson's trichrome to detect fibrosis. Telocytes were studied on tissue sections subjected to CD34 immunostaining. CD34/CD31 double immunofluorescence was performed to unequivocally differentiate telocytes (CD34‐positive/CD31‐negative) from vascular endothelial cells (CD34‐positive/CD31‐positive). Few telocytes entrapped in the fibrotic extracellular matrix were found in the muscularis mucosae and submucosa of SSc gastric wall. In the muscle layers and myenteric plexus, the network of telocytes was discontinuous or even completely absent around smooth muscle cells and ganglia. Telocytes were almost completely absent in fibrotic areas of SSc myocardium. In SSc fibrotic lung, few or no telocytes were observed in the thickened alveolar septa, around blood vessels and in the interstitial space surrounding terminal and respiratory bronchioles. In SSc, the loss of telocytes is not restricted to the skin, but it is a widespread process affecting multiple organs targeted by the fibrotic process. As telocytes are believed to be key players in the regulation of tissue/organ homoeostasis, our data suggest that telocyte loss might have important pathophysiological implications in SSc.